Herd Mentality Amongst Equity Investors During COVID-19: Evidences from Saudi Arabia - Alnori, Faisal; Ahmad, Moid U. (International Journal of Economics and Financial Issues, 2022)
The behaviour of individual equity investors during pandemics needs to be probed for better decision making. This study investigates the herd mentality amongst equity investors in Saudi Arabia in the context of COVID-19 (March 2020 to June 2021). The study is based on 326 responses and uses regression analysis as the anchor analytical technique. Additionally, the interaction of herding behaviour is probed in relation to overconfidence, emotions and independent decision making through a moderation analysis. The study found a negative moderating influence of age, gender and level of education on the herding behaviour of individual equity investors.